2014
DOI: 10.1007/s00213-014-3681-4
|View full text |Cite
|
Sign up to set email alerts
|

Time-course of extracellular nicotine and cotinine levels in rat brain following administration of nicotine: effects of route and ethanol coadministration

Abstract: Rationale Nicotine and ethanol are commonly coabused drugs, and nicotine-laced ethanol products are growing in popularity. However, little is known about time-course changes in extracellular nicotine and cotinine levels in rat models of ethanol and nicotine coabuse. Objectives The objective of the present study was to determine the time-course changes in brain levels of nicotine and cotinine following subcutaneous (SC) and intragastric (IG) nicotine administration in alcohol-preferring (P) and Wistar rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…The plasma analysis found that nicotine and cotinine levels 15 minutes after subcutaneous injection of 0.8 mg/kg were similar to those observed after 15 minutes of inhalation of vapor from 30 mg/mL in this study. The nicotine and cotinine levels were similar to intracerebral dialysate levels of nicotine and cotinine after subcutaneous injection of 0.7 mg/kg in Wistar rats (Katner et al, 2015) and plasma levels after a 0.03 mg/kg intravenous injection in Wistar rats (de Villiers et al, 2004). Concentrations of nicotine and cotinine in the plasma observed after 30 minutes of inhalation were significantly higher than those observed after 15 minutes of inhalation, confirming the control of dose via inhalation duration.…”
Section: Discussionsupporting
confidence: 66%
“…The plasma analysis found that nicotine and cotinine levels 15 minutes after subcutaneous injection of 0.8 mg/kg were similar to those observed after 15 minutes of inhalation of vapor from 30 mg/mL in this study. The nicotine and cotinine levels were similar to intracerebral dialysate levels of nicotine and cotinine after subcutaneous injection of 0.7 mg/kg in Wistar rats (Katner et al, 2015) and plasma levels after a 0.03 mg/kg intravenous injection in Wistar rats (de Villiers et al, 2004). Concentrations of nicotine and cotinine in the plasma observed after 30 minutes of inhalation were significantly higher than those observed after 15 minutes of inhalation, confirming the control of dose via inhalation duration.…”
Section: Discussionsupporting
confidence: 66%
“…The plasma analysis found that nicotine and cotinine levels 15 minutes after subcutaneous injection of 0.8 mg/kg were similar to those observed after 15 minutes of inhalation of vapor from 30 mg/mL in this study. The nicotine and cotinine levels were similar to intracerebral dialysate levels of nicotine and cotinine after subcutaneous injection of 0.7 mg/kg in Wistar rats (Katner et al 2015) and plasma levels after a 0.03 mg/kg intravenous injection in Wistar rats (de Villiers et al 2004).…”
Section: Discussionsupporting
confidence: 58%
“…Although nicotine levels were not measured in this study, extrapolation from data obtained in other nicotine self-administration studies (LeSage, Keyler, Collins, & Pentel, 2003; Shoaib & Stolerman, 1999) suggests that blood nicotine levels in the chow group are likely to be around 65 ng/mL, which is comparable to nicotine levels in smokers (Benowitz & Jacob, 1984). A recent study, showing that ethanol can affect nicotine accumulation in the brain, is consistent with the idea that ethanol is involved in nicotine addiction (Katner et al, 2015). …”
Section: Discussionsupporting
confidence: 83%